EPISTEMOLOGI PENDIDIKAN ISLAM - Siswanto, Siswanto (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
In the context of Islamic education, epistemology plays an important role in maintaining the honor of Muslims. Epistemology can awaken Muslims to reach the advancement of science and civilization. Epistemology of Islamic education is more directed at the use of methods or approaches to build and enhance the essence of this subject, both conceptually and applicative. Therefore, through Islamic epistemology, experts can do some fruitful actions, such as strengthening the theories or concepts of general education as well as Islamic education that is claimed to be criticized by using the approach they have, providing solutions to educational problems both theoretically and practically, discovering new concepts of Islamic education and developing the findings optimally. Thus, epistemology has great benefits to enhance the Islamic education which has distinctive features and unique characteristics on its curriculum and materials development. However, since Islam has its own education paradigm and purposes that differ from that of the West, automatically this will bring critical implications for the construction of educational conceptsÂ ÙÙ Ø§Ø·Ø§Ø± Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ©Ø ÙØ§Ø¨Ø³ØªÙÙÙÙØ¬ÙØ§ ÙØ¸ÙÙØ© ÙØ¨ÙØ±Ø© ÙÙØÙØ§Ø¸ Ø¹ÙÙ Ø¹Ø²Ø© Ø§ÙØ¥Ø³ÙØ§Ù. ÙØ§Ø³ØªØ·Ø§Ø¹ØªÂ  Ø£Ù ÙÙÙØ¶Øª Ø§ÙÙØ³ÙÙÙÙÂ Â  ÙÙØØµÙÙ Ø¹ÙÙ Ø§ÙØªÙØ¯Ù ÙÙ Ø§ÙØ¹ÙÙÙ ÙØ§ÙØØ¶Ø§Ø±Ø©. ÙÙÙØ¬ÙÙØª Ø§Ø¨Ø³ØªÙÙÙÙØ¬ÙØ©Â  Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø¥ÙÙ Ø§Ø³ØªØ®Ø¯Ø§Ù Ø§ÙØ·Ø±Ù ÙØ§ÙÙØ¯Ø§Ø®Ù ÙÙ Ø¨ÙØ§Ø¡ Ø§ÙØ¹ÙÙÙ Ø§ÙØªØ±Ø¨ÙÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙØ¸Ø±ÙØ© ÙØªØ·Ø¨ÙÙÙØ©. ÙØ¨ÙØ°Ù Ø§Ø³ØªØ·Ø§Ø¹ Ø®Ø¨Ø±Ø§Ø¡ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙÙÙØ§Ù Ø¨Ø£ÙÙØ± ÙÙÙØ§ : (1) ØªØµÙÙÙ Ø§ÙÙØ¸Ø±ÙØ§Øª Ø§ÙØªØ±Ø¨ÙÙØ© Ø¹Ø§ÙØ©Ø ÙØ§ÙÙØ¸Ø±ÙØ§Øª Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø®Ø§ØµØ© Ø§ÙØªÙ ÙÙÙÙ ÙÙØ¯ÙØ§ Ø¨Ø§ÙÙØ¯Ø®Ù ÙÙØ§ (2) ØªÙÙÙØ± Ø§ÙØÙÙÙ ÙÙÙØ¶Ø§ÙØ§ Ø§ÙØªØ±Ø¨ÙÙØ© Ø ÙØ¸Ø±ÙØ© ÙØªØ·Ø¨ÙÙÙØ© (3) Ø§Ø¨ØªÙØ§Ø± Ø§ÙÙÙØ§ÙÙÙ ÙØ§ÙÙØ¸Ø±ÙØ§Øª Ø§ÙØ¬Ø¯ÙØ¯Ø© ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© (4) ØªØ·ÙÙØ± ÙØ°Ù Ø§ÙØ§Ø¨Ø¯Ø§Ø¹Ø§Øª ÙØ¹Ø§ÙÙØ©. ÙØ¨ÙØ°Ø§ Ø§Ø³ØªØ·Ø§Ø¹Øª Ø§Ø¨Ø³ØªÙÙÙÙØ¬Ù Ø£Ù ØªØ±Ø§ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙØ§ÙØ¬Ø§Ø¯ Ø§ÙÙÙØ²Ø§Øª Ø§ÙØ®Ø§ØµØ© Ø¨ÙØ§ ÙÙ ØªØµÙÙÙ Ø§ÙØ£Ø³Ø³ ÙÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù Ø§ÙØ¥Ø³ÙØ§ÙÙ ÙØ§ÙØ£ÙØ¯Ø§Ù ÙÙÙ. ÙØ£Ù ÙØµØ§Ø¯Ø± Ø§ÙØ¹ÙÙÙ Ø§ÙØªÙ ÙØ¹ØªÙØ¯ Ø¨ÙØ§ Ø§ÙÙØ³ÙÙÙÙ ÙØ®ØªÙÙØ© Ø¹Ù Ø§ÙÙØµØ§Ø¯Ø± Ø§ÙØªÙ ÙØ¹ØªÙØ¯ Ø¨ÙØ§ Ø§ÙØºØ±Ø¨. ÙÙØ°Ø§ Ø³ÙØ¤Ø«Ø± ÙÙ Ø§ÙØ§Ø®ØªÙØ§Ù ÙÙ ØªØµÙÙÙ Ø§ÙÙØ¸Ø±ÙØ§Øª Ø§ÙØªØ±Ø¨ÙÙØ©.Â Â